Multiletramentos e contexto de escola pública : linguagem e sentidos nas e sobre as redes sociais - Ciavolella, Bruno (2015)
The theme of this study is the teaching of Portuguese, focusing on the integration of teaching practices that address the multiliteracies of digital culture. Although digital technology is increasingly pervading in everyday life, becoming part of local cultures, it is also observed that there are few teaching practices that aim to promote the multiliteracies in Portuguese classes. This situation reinforces the need for initiatives that include working with multiliteracies both in schools through pedagogical practices, and in the academic environment, through research. Considering these shortcomings, this work aims to analyze how the suggested encounters, through an action research, focusing on multiliteracies, (re)signified the teaching of Portuguese Language. Therefore, this research, qualitative in nature, is characterized as an action research, having the action objective to develop an educational practice in a public school of Paraná, in a class of eighth grade, consisting of 31 students. The pedagogical practice had, as object of teaching the multiliteracies in Facebook social network. Organized in two phases, the pedagogical practice, initially promoted the discussion on the recognition of local meanings attributed to social networks. In the second phase, in order to reflect on the construction of meaning and identity on Facebook, the practice consisted of reading activities aimed at discussing the social representations that can be made through a personal profile, in this case, the fanpage Homer Corintiano. The theoretical framework is the dialogical conception of language of Bakhtin Circle, the anthropological and cultural approach to literacy, according to the New Studies of Literacy (STREET, 2003, 2007, 2010, 2014), and the theory of multiliteracies (NEW LONDON GROUP, 1996; ROJO, 2013, 2013). The results show, concerning the involvement of students with multiliteracy practices of the digital culture, mainly the usage Facebook social network, as a performance space and expression of these adolescents in society, establishing itself as an important aspect in setting up their youthful lives. In the analysis of the responses to reading activities of pedagogical practice, verified that the activities enabled a meaning construction space in which we observed among the types of manifestations of responsive understanding, predominantly responses autonomously construction process as well as critical responses, thus demonstrating, student engagement in the proposed interlocutory game. However, in some of the reading issues, observed reproductive responses, which also indicate difficulty of making the reading activities in the classroom beyond the school barriers, being in a very active construction of meaning and citizenship.